Enantioseparation of pesticides: A critical review - Carrão, Daniel Blascke; Perovani, Icaro Salgado; de Albuquerque, Nayara Cristina Perez; de Oliveira, Anderson Rodrigo Moraes [UNESP] (Elsevier, 2020)
The potential of chiral pesticides to exhibit stereoselective behavior in regards to activity, toxicity, degradation, bioaccumulation, and/or metabolism has inspired numerous studies, e.g., several works have investigated the contamination of water, food, and soil by chiral pesticides and the consequences of non-targeted species (including human) exposure to these chemicals. As these studies typically rely on enantioselective separation methods such as liquid chromatography, supercritical fluid chromatography, gas chromatography, and capillary electromigration techniques, this review aims to provide a critical point of view on these analytical techniques used for the enantioselective analysis of pesticides. Accordingly, we selected papers from different areas and several issues (as chiral stationary phases or chiral selectors, mobile phases, and method detectability) regarding each technique were critically discussed. Finally, we outlined the future trends for each technique in the chiral analysis of pesticides.
Keywords: Capillary electromigration techniques; Chiral analysis; Chiral stationary phase; Enantiomer; Enantioselective; Gas chromatography; Liquid chromatography; Mass spectrometry; Pesticide; Supercritical fluid chromatography